The Influence of the Brainstorming Learning Model on Mathematical Communication Skills and Linguistic Intelligence - Salsabila, Salsabila; Mufidah, Zulfa; Netriwati, Netriwati (Universitas Ma'arif Lampung, 2024)
Mathematical communication skills are essential for students learning mathematics, but many have low mathematical communication skills. This quasi-experimental design research aims to determine the influence of the brainstorming learning model and linguistic intelligence on mathematical communication abilities and the interaction between the brainstorming learning model and linguistic intelligence on mathematical communication abilities. This research involved class VIII students at Ma'arif 10 Bangunrejo Junior High School for the 2023/2024 academic year with a research sample of 55 students (27 class VIII A students as the experimental class and 28 class VIII B students as the control class). Mathematical communication skills data was obtained using an essay test, while linguistic intelligence data was obtained using a questionnaire. The collected data was analyzed using the Two Way Anava statistical test with a significance level of 0.05, where before testing, it was found that the data was normally distributed and homogeneous. The results of this research inform that the brainstorming learning model affects mathematical communication skills, while linguistic intelligence does not affect mathematical communication skills. Furthermore, there is no interaction between the brainstorming learning model and linguistic intelligence on mathematical communication abilities.